Prevalence and determinants of diabetes and prediabetes among Vietnamese adults - Pham, Ngoc Minh; Eggleston, Karen (Diabetes research and clinical practice, 2016)
•We identified prevalence and risk factors of diabetes and prediabetes.•We projected the prevalence rates of diabetes and prediabetes for 2035.•Standardized prevalence rates of diabetes and prediabetes were 6.0% and 13.5%.•The projected prevalence of diabetes and prediabetes for 2035 were 7.0% and 15.7%.•Advancing age, overweight/obesity, physical inactivity and urban area were major determinants. We estimated the prevalence of diabetes and prediabetes among Vietnamese adults, and quantitatively evaluated association with known risk factors. Subjects were 5602 men and 10,680 women in North Vietnam aged 30–69 years participating in community diabetes screening programs during 2011–2013. We calculated standardized prevalence rates and demographic projections for 2035, and used multinomial regression analysis to examine the associations of multiple risk factors with diabetes and prediabetes. The age-, sex- and area of residence-standardized prevalence of diabetes was 6.0% and of prediabetes was 13.5%, with higher prevalence among men than women. Population aging is projected to raise the prevalence of diabetes to 7.0% and of prediabetes to 15.7% by 2035. Older age, obesity, large waist-to-hip ratio and hypertension were each associated with higher prevalence of diabetes, whereas the opposite direction of association was observed for underweight and minority ethnicity. In addition, diabetes was positively associated with family history of diabetes in women, but inversely related to physically heavy work among men. One in 17 and one in 7 adults had diabetes and prediabetes, respectively, in Vietnam. Urbanization, population aging, increased adiposity, hypertension and sedentary work are associated with the increasing prevalence of diabetes.